P1-S1.38 Emergence of Neisseria gonorrhoeae isolates With decreased susceptibilities to Ceftriaxone and Cefixime in Canada - 2001–2010. (10th July 2011) - Martin, I; Sawatzky, P; Allen, V; Hoang, L; Lefebvre, B; Mina, N; Gilmour, M
Abstract : Background: In Canada, the susceptibilities for ceftriaxone and cefixime in Neisseria gonorrhoeae are gradually decreasing and there has been a shift in the modal minimum inhibitory concentrations (MICs) from 0.016 μg/ml in 2000 to 0.032 μg/ml in 2008. We examined the phenotypic and genetic characteristics of N gonorrhoeae with decreased susceptibilities to 3rd generation cephalosporins isolated in Canada between 2001 and 2010. Methods: N gonorrhoeae isolates were collected by Canadian provincial public health laboratories. MICs were determined by agar dilution at the National Microbiology Laboratory (NML) and isolates displaying decreased susceptibilities to cefixime (MIC=0.25 mg/l and 0.5 mg/l) and ceftriaxone (MIC=0.125 mg/l and 0.25 mg/l) were examined using multi-antigen sequence typing (NG-MAST) and sequencing of resistance determinants associated with decreased cephalosporin susceptibilities (penA, mtrR, ponA, porB). Results: A total of 155 N gonorrhoeae isolates with decreased susceptibility MICs to ceftriaxone and cefixime were identified from the following provinces - Ontario (53.5%, N=83); British Columbia (34.2%, N=53); Québec (12.3%, N=19). Of the 155 isolates observed with reduced susceptibility, 23 were observed between 2001 and 2007 (14.8%), whereas in 2008, 2009 and 2010 there were 84 isolates (54.2%), 23 isolates (14.8%) and 25 isolates (16.1%) observed, respectively. Thirty-eight different NG-MAST sequence types were identified among the isolates; ST-3158, ST-225 and ST-1407 were the most prevalent at 25.9%, 19.4% and 14.8%, respectively. The mtrR resistance determinants were present in 95.5% of the isolates. The penA mosaic was present in 60% of the isolates, with the most common penA mosaic types XXXII and X identified at 51.0% and 7.7%, respectively, while the non-mosaic penA type XII was identified in 36.8% of the isolates. The G101K alteration in porB was present in 97.4% of the isolates and the A102N and A102D alterations in porB were found in 49.7% and 45.8% of the isolates, respectively. L421P alterations in ponA were present in all the isolates. Conclusions: In Canada, N gonorrhoeae isolates with decreased susceptibilities to 3rd generation cephalosporins, including cefixime and ceftriaxone have increased over the years. The alterations in penA, mtrR and porB are important determinants identified in these isolates. The most common ST types identified among these Canadian isolates have also been reported worldwide.